The co-carcinogenic effect of topical vitamin A palmitate on 9, 10-dimethyl-1, 2-benzathracene (DMBA)-induced carcinoma in the buccal pouch of the syrian golden hamster - Polliack, Aaron (Department of Medicine, 2020)
Salley in 1954, (122) was the first worker to use the hamster cheek pouch as a model for experimental carcinogenesis and to produce squamous cell carcinomas in this organ. For a number of reasons, the pouch is most suitable for sequential studies of carcinogenesis, and these include the fact that it is easily accessible and can be everted simply, facilitating macroscopic examination. Furthermore, its anatomic situation makes it a simple model for topical application of any carcinogen. Each animal has two pouches, thus providing its own control. In addition, the pouch serves as a storehouse and is lined only by stratified squamous epithelium with no glands or hair follicles in its wall, thus rendering it less susceptible to cyclic changes than more complex tissues, in which accessory structures are present.